Ahammiyah al-Balagah al-’Arabiyah fi tafsir al-Qur’an - Ahmad Syatibi (Insaniyat : Journal of Islam and Humanities, 2016)
The  Qur’an  was  revealed  in  Arabic.  This  holy  book  has  two  main  objectives:  as  God’s miracle  and  as  an  evidence  of  the  prophethood  of  His  last  messenger,  Muhammad.  As  a miracle,  all  of  the  Qur’anic  verses  are  God’s  guidance.  The  guidance  and  miracle  of  the Qur’an is traceable in its balaghoh (rhetoric). Understanding this rhetoric will guide people to  know  about  what  to  do  or  not  to  do  according  to  this  book.  To  learn  the  Qur’an  as guidance  from  its  rhetoric,  people  are  to  live  on  their  lives  according  to  the  Qur’anic teachings.  The  balaghoh  is  a  foundation  to  grasp  and  reveal  the  meaning  of  the  Qur’an.DOI: 10.15408/insaniyat.v1i1.4509